Perception and Attitude of Students toward the Learning and Teaching . of French Language as a General Course in Universities: Afe Babalola University as a Case Study - Oyeniyi, Toluwalope (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Attitude and perception oflearners determine how they learn a target language. The perceived importance of the language also determines the way the learner learns it. However, this study aims at examining the perception and attitude of students of Afe Babalola University, Ado-Ekiti (ABU AD) towards the teaching and learning of French language as a general course. The descriptive survey research was employed and a self-structured modified questionnaire was used to elicit information from respondents. A total of two hundred and seven (207) undergraduate students of ABUAD were surveyed by a simple random sampling technique. Upon the completion of data, it was analyzed, computed, and tabulated using frequency counts and percentage. The findings suggest that the respondents are aware of the importance and benefits of learning French language. This is reflected in the fairly positive attitude shown towards the teaching and learning of French language as a general course.